2010
DOI: 10.1017/s1461145710000921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjunct galantamine to risperidone, or haloperidol, in animal models of antipsychotic activity and extrapyramidal side-effect liability: involvement of the cholinergic muscarinic receptor

Abstract: The acetylcholine esterase inhibitor/cholinergic nicotinic receptor (nAChR) allosteric modulator galantamine (Gal) is used against cognitive impairment in Alzheimer's disease. Negative/cognitive and psychotic symptom improvement in schizophrenia by adjunct Gal to antipsychotic drugs (APDs) has been reported. Cognitive symptoms in schizophrenia may involve brain prefrontal hypo-dopaminergia. Experimental data by others indicate nAChR involvement in animal pro-cognitive effects of Gal. The role of nAChRs in anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…We have found that galantamine improves apomorphine-and isolation rearing-induced PPI deficits via an activation of the muscarinic receptors, especially M 1 (34,75). In addition, Wadenberg et al (66) recently reported that pretreatment with scopolamine, but not mecamylamine, completely reversed the enhancing effects of galantamine, when co-administered with haloperidol, in the conditioned avoidance response test. Although the inhibitory effect of galantamine on acetylcholinesterase is weak, microdialysis studies show that systemic administration of galantamine increases the extracellular ACh levels in mice (34) and rats (30).…”
Section: Schizophreniamentioning
confidence: 61%
See 1 more Smart Citation
“…We have found that galantamine improves apomorphine-and isolation rearing-induced PPI deficits via an activation of the muscarinic receptors, especially M 1 (34,75). In addition, Wadenberg et al (66) recently reported that pretreatment with scopolamine, but not mecamylamine, completely reversed the enhancing effects of galantamine, when co-administered with haloperidol, in the conditioned avoidance response test. Although the inhibitory effect of galantamine on acetylcholinesterase is weak, microdialysis studies show that systemic administration of galantamine increases the extracellular ACh levels in mice (34) and rats (30).…”
Section: Schizophreniamentioning
confidence: 61%
“…Wiker et al (65) reported that galantamine at doses of 5 mg/kg alone attenuated the conditioned avoidance response, and at lower doses (1 mg/kg) it potentiated typical antipsychotic racloprideinduced avoidance response in rats. In addition, adjunctive galantamine (1.25 mg/kg) also enhanced the antipsychotic-like effects of haloperidol and risperidone in the conditioned avoidance response test (66).…”
Section: Schizophreniamentioning
confidence: 94%
“…The followup study, however, demonstrated that any contribution to antipsychotic activity through galantamine is primarily mediated via muscarinic, but not nicotinic, acetylcholine receptors (Wadenberg et al, 2011). Nevertheless, α7-nAChRs might also participate in antipsychotic activity because the α7-nAChR agonist WYE-103914/SEN34625 potentiated the efficacy profile of risperidone in the CAR test (Marquis et al, 2011).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
“…Interestingly, galantamine has been reported to act partly on muscarinic receptor subtypes in some situations (Almasieh et al ). Indeed, Wadenberg et al () have shown that the potentiation by galantamine of antipsychotic drug efficacy in conditioned avoidance testing is prevented by muscarinic but not nicotinic receptor blockers, leading to their proposal that anti‐psychotic activity of galantamine involves mainly muscarinic receptors. This would be supported by evidence that the abnormal pre‐pulse inhibition seen in mice reared in isolation is normalised by a muscarinic action of galantamine (Yano et al ) and is not affected by a different acetylcholinesterase inhibitor such as donepezil (Koda et al ).…”
Section: Galantamine As a Pharmacological Toolmentioning
confidence: 99%